Hydrogen Sulfide Affects Radical Formation in the Hippocampus of LPS Treated Rats and the Effect of Antipsychotics on Hydrogen Sulfide Forming Enzymes in Human Cell Lines - Sommer, Olaf; Aug, Rosana L.; Schmidt, Andreas J.; Heiser, Philip; Schulz, Eberhard; Vedder, Helmut; Clement, Hans-Willi (Frontiers in Psychiatry, 2018)
Objectives Psychiatric disorders such as schizophrenia and other neuroinflammatory diseases are accompanied by metabolic, free radical or neuronal changes. Hydrogen sulfide (H2S) is a peripheral and central nervous endogenously produced gaseous molecule through cysteine by cystathionine-y¬lyase (CSE), cystathionine ß-synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (MPST) the major H2S producing enzyme in the brain. The physiological effects of H2S are broad, with antioxidative properties being the major role in the body. Aims of our investigation were to analyze central nervous antioxidant, metabolic and neuronal effects in the hippocampus of the rat after inflammatory peripheral lipopolysaccharide (LPS) treatment and the effects of antipsychotics on the expression of these enzymes in human cell lines. Material and Methods Male Lewis rats (250g) received an i.p. LPS injection (1mg/kg) 24h before microdialysis experiments. Conscious rats were infused via these probe (1.5µl/min) with a radical scavenger 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine (CMH) in Krebs-Ringer solution. Sodiumhydrogensulfide (NaHS, 10 µg/min.) was infused after 2 h baseline for one hour. Corticosterone, glutamate, glucose and lactate were measured by Elisa. Reactive oxygen species (ROS) were detected by electron spin resonance spectroscopy. In human neuroblastoma SH-SY5Y and monocytic U-937 cell lines the impact of the antipsychotics haloperidol, clozapine, olanzapine and risperidone on the expression of genes encoding the key enzymes of H2S synthesis was studied. The cells were incubated for 24 h with 30 µM antipsychotic; mRNA levels were measured by polymerase chain reaction. Results Microdialysate glucose and lactate levels were dramatically increased in the hippocampus of LPS untreated rats by local application of NaHS while in the LPS pretreated rats there was no effect of NaHS infusion on glucose but a further significant increase in microdialysate lactate. LPS pretreatment alone enhanced particularly lactate levels. Hippocampal microdialysate glutamate levels were highly increased after local NaHS infusion in LPS untreated animals. In LPS treated rats no change was observed by NaHS, but LPS itself had the strongest effect on microdialysate glutamate levels. Microdialysate corticosterone levels were reduced by NaHS in both LPS pretreated and untreated rats. The formation of free radicals in the hippocampus was significantly reduced in LPS pretreated rats, while in LPS untreated rats